Factors influencing consumer intention to sort household waste: A Brazilian perspective - Delgado, Fernanda Camila Martinez [UNESP]; Bezerra, Barbara Stolte [UNESP]; Baldan, Juliana Santiago [UNESP]; Moretti Ribeiro da Silva, Hermes [UNESP]; Barriga, Gladys Dorothea Cacsire [UNESP] (SAGE Publications, 2024)
Effectively sorting and recycling waste has consequently emerged as a key strategy for environmental preservation and the creation of sustainable communities. The current study aimed to examine the factors influencing consumers’ intentions to sort household waste, utilizing the theory of planned behaviour. Collecting 300 responses from Brazilian consumers through structured questionnaires, the study employed a partial least square structural equation modelling approach to assess the proposed hypotheses. The findings emphasized the significant impact of the perceived cost and benefit factor, alongside the influence of information on proper waste disposal (perceived effectiveness), as communicated by entities managing selective waste collection. These findings emphasize the key role of effective communication from waste management agency regarding the outcomes of domestic waste separation efforts for recycling, as well as the perceived benefits and costs by consumers. Such communication is essential for fostering and maintaining consumer engagement in recycling initiatives.
Keywords: circular economy; Consumer behaviour; structural equation modelling; waste sorting; 'current; Circular economy; Environmental preservation; Household waste; Perceived benefits; Perceived costs; Recycling wastes; Structural equation models; Sustainable communities; Waste sorting